Effects of pharmacological neurotrophin receptor inhibition on bladder function in female mice with cyclophosphamide-induced cystitis - Hsiang, Harrison W.; Girard, Beatrice M.; Ratkovits, Lexi; Campbell, Susan E.; Vizzard, Margaret A. (Frontiers in Urology, 2022)
Interstitial cystitis/bladder pain syndrome is a chronic inflammatory pelvic pain syndrome of unknown etiology characterized by a number of lower urinary tract symptoms, including increased urinary urgency and frequency, bladder discomfort, decreased bladder capacity, and pelvic pain. While its etiology remains unknown, a large body of evidence suggests a role for changes in neurotrophin signaling, particularly that of nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF). Here, we evaluated the effects of pharmacological inhibition of the NGF receptor TrkA, BDNF receptor TrkB, and pan-neurotrophin receptor p75NTR on bladder function in acute (4-hour) and chronic (8-day) mouse models of cyclophosphamide (CYP)-induced cystitis. TrkA inhibition via ARRY-954 significantly increased intermicturition interval and bladder capacity in control and acute and chronic CYP-treatment conditions. TrkB inhibition via ANA-12 significantly increased intermicturition interval and bladder capacity in acute, but not chronic, CYP-treatment conditions. Interestingly, intermicturition interval and bladder capacity significantly increased following p75NTR inhibition via LM11A-31 in the acute CYP-treatment condition, but decreased in the chronic condition, potentially due to compensatory changes in neurotrophin signaling or increased urothelial barrier dysfunction in the chronic condition. Our findings demonstrate that these receptors represent additional potent therapeutic targets in mice with cystitis and may be useful in the treatment of interstitial cystitis and other inflammatory disorders of the bladder.